Impact of employee competency, budget planning, and ERP on the budget implementation performance - Yunaniah, Luk Luatun; Firmansyah, Amrie (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study analyzes the impact of employee competency, budget planning, and enterprise resource planning (ERP)-based information systems on the performance of budget implementation in state financial management. Method: A quantitative approach was used, with data collected via a survey questionnaire distributed in December 2023. The questionnaire used a Likert scale ranging from 1 to 6. Respondents were selected through purposive sampling, targeting officials or staff managing state finances in the Working Unit of the Bureau for General Affairs and Procurement Goods/Service of the Ministry of Marine Affairs and Fisheries of Indonesia. The final sample consisted of 32 observations and was analyzed using SmartPLS 3.0. Results: The study found that Employee competency positively impacts budget implementation performance in state financial management. However, budget planning and ERP-based information systems did not significantly influence budget implementation performance. Limitations: The sample size of the study was limited because of the limited time for data collection. Furthermore, the study focused solely on officials responsible for managing state finances, excluding Budget Planners and Procurement Officers, who also played a vital role in the budget process.   Contribution: This study provides valuable insights for future studies and serves as a reference for improving government performance. It also offers practical recommendations for decision makers. Novelty: This study introduces new indicators based on current regulations, focusing on ERP-based systems in Indonesia's public sector. The SAKTI system, an ERP-based budget implementation tool, was fully implemented across all Ministries/Agencies in Indonesia by 2022, making this study particularly timely.